Zinc borate production with boron mineral source: effect of process parameters on yield and hydrophobicity - Acarali, Nil Baran; Ozturk, Emre; Bardakci, Melek; Piskin, Mehmet Burcin; Tugrul, Nurcan (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, MINER & ENERGY ECON RES INST PAS, 2015)
The aim of this study was to synthesize zinc borate by using zinc carbonate, boric acid, reference zinc borate (reference ZB) as seed and to investigate effects of modifying agents and reaction parameters on hydrophobicity and yield, respectively. Different from the studies available in the literature, the effects of different modifying agents (propylene glycol (PG) (0-6%), kerosene (1-6%), oleic acid (OA) (1-6%)) with solvents (isopropyl alcohol (IPA), ethanol, methanol) added to reaction on hydrophobicity were investigated comparingly. Firstly, the effects of reaction parameters such as reaction time (1-5 h), reactant ratio (H3BO3/ZnO) (2-5), seed ratio (0-1.5%, in terms of boric acid, w/w), reaction temperature (323-393 K), cooling temperature (283-353 K) and stirring rate (400-700 rpm) on yield were investigated. Furthermore, reactions were carried out under determined reaction conditions in both magnetically and mechanically stirred systems. The product, zinc borate, was characterized by analytical methods, XRD (X-ray Diffraction), FT-IR (Fourier Transform Infrared Spectroscopy) techniques and measurement of contact angle which identified hydrophobicity was carried out. In conclusion, it was observed that zinc borate was synthesized successfully and different modifying agents with various solvents affected the hydrophobicity of zinc borate.
Keywords: hydrophobicity; yield; zinc borate; zinc carbonate; BORIC-ACID; AQUEOUS-MEDIUM; OXIDE; 2ZNO-CENTER-DOT-3B(2)O(3)CENTER-DOT-3H(2)O; Mineralogy; Mining & Mineral Processing